2019
DOI: 10.1080/13200968.2019.1667777
|View full text |Cite
|
Sign up to set email alerts
|

Queer Cases Unmake Gendered Law, Or, Fucking Law’s Gendering Function

Abstract: Law's role in upholding and continually reproducing the cisheteropatriarchy is increasingly being challenged in Western courts. This is happening directly, by 'non-gendered' claimants wishing to undo law's compulsory gender performance, and by 'birthing men' seeking to queer law's gender binary. Indirectly 'fucking' law's gendering function are the defendants in the so-called 'gender deception' prosecutions. Here we see the judicial system reasserting its hegemony as heteronormmaker and enforcer. A different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…By foregoing traditional judicial categories of obiter dicta and ratio decidendi in case law, in which the former is considered to be unimportant, Kalpana Kannabiran has argued that utterances of the judiciary from hard-won gains of movements of sexual and gender minorities are disruptions against the violent, misogynistic, and nationalist Indian state (Kannabiran 2019 ). Similarly, Grietje Baars has shown that judgments can perform a “queering function”, by challenging the form, function, and even the existence of gender and the gender binary in the law (Baars 2019 , 17).…”
Section: Constitutional Cases For Queer Domesticitiesmentioning
confidence: 99%
“…By foregoing traditional judicial categories of obiter dicta and ratio decidendi in case law, in which the former is considered to be unimportant, Kalpana Kannabiran has argued that utterances of the judiciary from hard-won gains of movements of sexual and gender minorities are disruptions against the violent, misogynistic, and nationalist Indian state (Kannabiran 2019 ). Similarly, Grietje Baars has shown that judgments can perform a “queering function”, by challenging the form, function, and even the existence of gender and the gender binary in the law (Baars 2019 , 17).…”
Section: Constitutional Cases For Queer Domesticitiesmentioning
confidence: 99%
“…Possibilities for bodily changes on a material level do, however, provoke challenges for legal and executive systems (Baars 2019). When a nation-state allows for legal changes to gender and to medically supported transition, other aspects of gender-sensitive legislation (including laws related to marriage, parenthood, adoption and divorce) may be challenged, and the question of legal discrepancies or individual integrity of the person before the law may arise.…”
Section: A New Legal Materials Turn?mentioning
confidence: 99%
“…63 Apart from the right of children to know their mother, the outcome sought by the applicants is understood to contravene more profoundly a 'right to a mother' which every child supposedly has. 64 The High Court elaborated on this point more vocally than the Court of Appeal 65 and explained that registering a trans man who gave birth as the child's 'father' or 'parent' implies that this child 'will not have, and will never have had, a "mother" as a matter of law, he will only have a father'. 66 According to English courts, this outcome would run counter to the child's best interests to have a mother and to know who that person is.…”
Section: Recent Developments Before Domestic Courtsmentioning
confidence: 99%